THE ROLE OF TERMA GENRE IN THE REPERTOIRE OF BAKHSHI (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article deals with the opinion about the Bakhshi performance repertoire of Uzbek folklore, the Terma genre, its uniqueness and types. Terma is the genre that prepares Bakhshi for the performance of epics and encourages the audience to listen to epics. They are created on a teacher-student basis as a separate genre of the epic type, which differs in the variety of Terma themes and formal structure and it is expressed the scientific-theoretical views about the factors.